Responding to affected people during the pandemic ADB accountability mechanism annual report 2020. (ADB accountability mechanism annual reports., 2021)
Under ADB Accountability Mechanism, the two offices adjusted processes to allow complainants to continue expressing their concerns, seek solutions to problems, and report noncompliance with ADB operational policies and procedures during the COVID-19 pandemic. Despite of challenging circumstances, the Office of the Special Project Facilitator and the Office of the Compliance Review Panel continue to conduct outreach activities and capacity building to strengthen ADB response mechanism and ensure the safety and security of people from project-affected areas in Asia and the Pacific.